About 1/3rd of north Indian patients less than 50 years of age with type 2 diabetes have high pulse wave velocity indicating high risk of atherosclerosis. Issue 6 (November 2020) - Gupta, Ritesh; Tyagi, Kanika; Anoop, Shajith; Ghosh, Amerta; Misra, Anoop
Abstract: Background and aims: Asian Indian patients with type 2 diabetes mellitus (T2DM) have a high cardiovascular risk even at young age. There is a need to assess this increased risk and identify atherosclerosis early so that appropriate measures for risk reduction can be taken. We aimed to study carotid-femoral pulse wave velocity (Cf-PWV), a non-invasive indicator of atherosclerosis, in patients with diabetes below 50 years of age and its correlation with markers of obesity and other cardiovascular risk factors. Methods: Patients (n, 299) with T2DM below 50 years of age underwent measurement of Cf-PWV by applanation tonometry. Anthropometric parameters, blood pressure, liver span, glycosylated hemoglobin, serum lipid profile, urinary microalbumin, ankle brachial index and carotid intima media thickness were measured. Results: Data show that 32.4% of patients had high Cf-PWV, with mean values higher in males than females. On stepwise multiple linear regression analysis, the significant independent determinants of PWV were age, systolic blood pressure, waist circumference, microalbumin and liver span. Conclusion: About one third patients with T2DM less than 50 years of age, in north India have increased arterial stiffness which correlates with blood pressure, abdominal obesity, liver size and microalbumin, indicating increased risk for coronary artery disease. Highlights: One third of patients with type 2 diabetes less than 50 years had increased pulse wave velocity (PWV). PWV correlated with age, blood pressure, abdominal obesity and liver size. High PWV in young people with diabetes indicates a high risk of atherosclerosis.